A Fuzzy Decision-Making Framework for Route Selection in Multimodal Transportation Networks. Issue 4 (2nd October 2022) - Koohathongsumrit, Nitidetch; Meethom, Warapoj
Abstract: This study presents a novel decision-making framework for route selection in multimodal transportation networks under fuzzy environments. The proposed framework integrates the fuzzy group decision-making technique, the fuzzy deliberate process, and fuzzy multiple criteria decision-making approaches. Hence, the fuzzy Delphi method, fuzzy risk assessment, the fuzzy analytic hierarchy process, and the fuzzy technique for order of preference by similarity to ideal solution are first combined to select the most appropriate multimodal route. An empirical study demonstrates that the proposed framework is an outstanding and systematic decision support tool to aid decision makers in transportation decision-making processes of freight route selections.